Examination of Neopterin and TNF-Alpha Levels in Preeclampsia Cases - Sapmaz, Ekrem; Bulut, Vedat; Celik, Aygen; Akbulut, Handan; Ilhan, Nevin; Hanay, Fethi (Galenos Yayincilik, 2006)
Objective: To examine serum neopterin and TNF- alpha levels of pregnant women diagnosed as preeclampsia and healthy pregnant women in a similar week of pregnancy. Setting: Firat University, School of Medicine, Obstetrics and Gynaecology Department, Elazig. Material and method: A total of 120 pregnant women were included in a randomized bloc designed, cross-sectional and prospective study. Of the women, 60 were those diagnosed as preeclampsia (G1=mild preeclampsia, n=20; G2=severe preeclampsia, n=20; G3=eclampsia, n=20) and 60 were healthy pregnant women in the same pregnancy week (G4=control of G1, n=20; G5=control of G2, n=20; G6=control of G3, n=20). Neopterin and TNF-alpha levels were examined in the maternal serum. Each preeclampsia group was compared first with its own control group (G1-G4, G2-G5, G3-G6) and then with one another (G1-G2, G1-G3, G2G3). Mann Whitney U test was used in the comparison of continuous and ordinal data. Results: TNF-alpha levels were found significantly higher in the preeclampsia groups, when compared to the control groups (G1-G4, G2G5, G3-G6=p<0,05, Mann Whitney U test). However, the comparison of preeclampsia groups among themselves did not show a statistical difference (p>0,05, Kruskall Wallis variance analysis). Neopterin levels in the mild preeclampsia group were similar to those in its control group (G1-G4=p>0,05, Mann Whitney U test), but significantly higher in the other groups in comparison to their controls (G2-G5, G3G6=p<0,05, Mann Whitney U test). When preeclampsia groups were compared with each other, a significant increase was established in severe preeclampsia and eclampsia groups relative to mild preeclampsia group (G1-G2, G1-G3=p<0,03, Mann Whitney U test). Conclusion: TNF-alpha levels in the maternal serum significantly increase in preeclamptic and eclamptic pregnant women, in comparison to healthy pregnant women, but there is no significant difference between preeclampsia and eclampsia groups. Neopterin levels increase both in comparison to the healthy pregnant women and among themselves, in severe preeclampsia and eclampsia groups, but not in the mild preeclampsia group.
Keywords: eclampsia; neopterin; TNF-alpha; preeclampsia; T helper 1/T helper 2 activity